Drivers, development, and impact of tillering plasticity mechanisms for corn yield stability in Kansas environments - Veenstra, Rachel Lynn (Kansas State University, 2022)
Historic breeding efforts in corn (Zea mays L.) have resulted in uniform, single-stalked phenotypes with limited environmental plasticity potential. Therefore, plant density is a critical yield component for corn, as it is unable to successfully compensate for a deficit of grain-bearing shoots. Enhancing corn yield stability across plant densities has potential benefits, particularly considering diverse yield environments and seasonal weather uncertainties due to climate change. Research and actionable information regarding branching (“tillering”) utility in corn production are largely unavailable. This is particularly relevant in environments where plant density is typically resource-limited or environments in which the target density is not properly achieved. Therefore, the objectives of this dissertation were to determine the following based on tillered corn phenotypes in a range of environment (E) x management (M) scenarios: 1) the impact of tiller development on corn yields; 2) the plastic extent and relative importance of yield components; 3) the drivers and predictability of corn tiller development; and 4) the effect of tiller expression on biomass accumulation, carbon economy, and subsequent reproductive efficiency. This extensive field study evaluated tiller presence (removed or intact) with two commercial hybrids (P0657AM and P0805AM, Corteva Agriscience, Johnston, IA) in a range of plant densities (25000, 42000, and 60000 pl ha⁻¹) across the state of Kansas. In total, 17 site-years were evaluated – comprised of 9 unique field locations across 3 seasons (2019-2021). Yields were increased or unaffected by greater plant densities and tiller presence. Environments varied in yield responsiveness to tiller density, but plant density was key to maximizing yield. Favorable soil properties and higher photothermal quotient (PTQ) values were important correlates of tiller productivity (Chapter 2). Ear number and kernel number per area were less dependent on plant density with tillered phenotypes. Kernel number remained key to yield stability. Although ear number was less related to yield stability, ear source and type were significant yield predictors, with tiller axillary ears as stronger contributors than main stalk secondary ears in high-yielding environments (Chapter 3). Plant density interactions with cumulative growing degree days (GDD), PTQ, mean minimum and maximum daily temperatures, cumulative vapor pressure deficit (VPD), soil nitrate (NO₃), and soil phosphorus (P) were important predictive factors of tiller density – many of these with stark non-limiting thresholds. Out-of-season prediction errors were seasonally variable, highlighting the importance of representative training datasets (Chapter 4). Tiller expression stabilized aboveground biomass across plant densities at the hectare scale. Greater tiller biomass was not correlated with any changes in reproductive efficiency. Additional stem tissue allowed tillered corn phenotypes to accumulate a greater reserve of water-soluble carbohydrates in low plant densities and support main stem remobilization demand (Chapter 5). Overall, tillering in corn presents itself as a potentially useful plasticity mechanism in non-uniform field situations with unexpectedly reduced or inadequate plant densities. While limits to tiller productivity are apparent, the branching ability of modern corn hybrids may lend itself to improving resilience of defensive strategies in water-limited environments. It should be noted that although this study explored a range of environments, severe drought scenarios were not explored. The utility of tillering as a plasticity mechanism in corn remains an area of active study.
Keywords: Corn; Tillering; Crop plasticity; Yield; Yield components; Carbohydrates